Crisis Management Strategies to Overcome Market Disruption in the Digital Age - Sumarno Sumarno; Sawal Sartono; Kusna Djati Purnama; Muhammad Aqshel Revinzky; Dwi Ermayanti Susilo; Jumroni Jumroni (Maneggio, 2025)
This study aims to analyze the implementation of crisis management strategies in the digital age with a focus on the role of technology in helping companies deal with market disruptions and maintain business sustainability. This study uses a qualitative approach by conducting in-depth interviews with 10 respondents from various business sectors, including retail, MSMEs, and services. The results showed that proactive strategies, such as business model innovation and product diversification, as well as responsive strategies, such as organizational restructuring and digital communications, played an important role in dealing with the crisis. Digital technologies, such as cloud computing, social media, and big data analytics, are proving to be key elements supporting the effectiveness of crisis management, although some companies face constraints such as infrastructure limitations, employee resistance, and a lack of digital expertise. In addition, Adaptive Leadership and cross-divisional collaboration are important factors that determine success. This research contributes to the development of crisis management strategies that are more effective and relevant in the digital age, especially to increase the competitiveness and resilience of companies to market disruption.